1983
DOI: 10.1016/0092-8674(83)90218-0
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for intrachromosomal gene conversion in cultured mouse cells

Abstract: In this report we present an experimental scheme that facilitates the study of homologous recombination between closely linked genes in cultured mammalian cells. Two different Xho I linker insertion mutants of the herpes simplex virus type 1 thymidine kinase (HTK) gene were introduced into mouse LTK- cells as direct repeats on a plasmid carrying a dominant selectable marker. Following stabilization of these sequences in the recipient cell, selection for TK+ was applied to detect recombinational events between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
67
1

Year Published

1984
1984
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(71 citation statements)
references
References 32 publications
3
67
1
Order By: Relevance
“…The average gene conversion frequency (Table 3) was approximately fivefold higher than the average single-crossover frequency we have measured earlier (20). This result is consistent with those of Liskay et al (10,11), who found that gene conversion between defective tk genes occurred more frequently than reciprocal recombination. The gene conversion frequencies in Table 3 were 16-to 67-fold higher than the background reversion frequency of the neoX gene.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The average gene conversion frequency (Table 3) was approximately fivefold higher than the average single-crossover frequency we have measured earlier (20). This result is consistent with those of Liskay et al (10,11), who found that gene conversion between defective tk genes occurred more frequently than reciprocal recombination. The gene conversion frequencies in Table 3 were 16-to 67-fold higher than the background reversion frequency of the neoX gene.…”
Section: Discussionsupporting
confidence: 81%
“…Recent experiments on chromosomal homologous recombination in a number of laboratories have relied on the use of either overlapping truncated fragments or mutant copies of the herpesvirus thymidine kinase (tk) (9)(10)(11) or neomycin resistance (neo) gene (16,20) to detect recombination events which restore one or more copies of the selected marker gene. Although these studies have measured recombination frequencies and characterized various reciprocal and nonreciprocal intrachromosomal recombination events, attempts to estimate the true frequencies of these events have been complicated by the ability of the recombination substrates to undergo both reciprocal and nonreciprocal recombination.…”
mentioning
confidence: 99%
“…A possible explanation comes from experiments using yeast, in which the probability that a heterozygous recessive gene becomes homozygous is two orders of magnitude higher for nonreciprocal recombination than for gene mutation (22,23). Also, observations in cultured mouse cells showed that the frequency of nonreciprocal recombination (gene conversion) between repetitive genes is several orders of magni- tude higher than the frequency of gene mutation (24). With reciprocal recombination, a single event is sufficient to result in the expression of all recessive mutations of a chromosomal segment, whereas with gene mutations several single events would be needed to achieve a similar effect.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that mammalian cells in culture have a highly efficient machinery which promotes homologous recombination between exogeneous DNA molecules (10,(16)(17)(18). Recombination should therefore occur between the circular plasmid molecules added to the cells.…”
Section: Methodsmentioning
confidence: 99%